Does Accounting Comparability Affect Corporate Employment Decision-Making? - Mohamed Elmagrhi (The British Accounting Review, 2020)
This paper investigates whether accounting comparability affects corporate employment decision-making. We find that firms with greater accounting comparability experience a lower degree of inefficiency in labour investments. Further, our results show that accounting comparability affects labour investments via improved external monitoring and internal governance mechanisms. Additional analyses indicate that our findings are not driven by non-labour investments and are robust to alternative explanations and endogeneity concerns. Collectively, the results are consistent with the view that comparability is an effective monitoring tool, which mitigates agency conflict and thereby reduces opportunistic employment decision-making.